Cluster Preface: Functional Dyes - Yang, Youjun; Fan, Jiangli (Synlett, 2023)
Youjun Yang (left) received his BS (2002) from the University of Science and Technology of China, and his PhD (2007) with Prof. Robert M. Strongin at Louisiana State University. Then, he joined the Anslyn group at UT Austin as a postdoc. In 2010, he joined the faculty of the school of pharmacy, East China University of Science and Technology (ECUST). His research interests include NIR fluorescent dyes, photo-responsive dyes, and fluorescent molecular probes.Jiangli Fan (right) obtained her PhD at Dalian University of Technology (2005). Now she is a Professor at the School of Chemical Engineering at Dalian University of Technology, and she received the Distinguished Young Scholars of NSFC (2019). Her research interests mainly focus on the development of functional dyes for biomedical analysis and disease treatment.